Detecting fraudulent financial reporting: Heptagon fraud model - Pamungkas, Imang Dapit; Irwandi, Soni Agus (Universitas Hayam Wuruk Perbanas, 2024)
This study aims to examine the role of corporate governance mechanisms in detecting fraudulent financial reporting (FFR) based on the fraud heptagon model. Quantitative method is used to analyze secondary data obtained from annual reports of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange for the period of 2019-2022. Sampling is carried out using purposive sampling method. This study uses 80 samples which are processed using WarpPLS 8.0 with the logistic regression analysis method. The results show that pressure and rationalization have an effect on fraudulent financial reporting. In contrast, other elements such as opportunity, capabilities, arrogance, ignorance, and greed do not have a significant effect on fraudulent financial reporting. Corporate governance mechanisms only moderate the effect of arrogance and ignorance on fraudulent financial reporting. It is expected that regulatory authorities in State-Owned Enterprises understand the reliability of the fraud heptagon model in detecting financial reporting fraud and provide guidance on fraud detection priorities. The novelty of this study is that it places corporate governance mechanisms as a moderating variable in the effect of fraud heptagon model on financial reporting fraud in State-Owned Enterprises in Indonesia.